Examination of the optimal power flow based facts devices : optimal location of facts, power quality, global optimization merthds, decomposed network, planning and cntrol - Belkacem, M. (Berlin : LAP Lambert Academic Publishing, 2010)
During the last years, as power demand grow, the power systems become increasingly more difficult to operate within the indices power quality, and the system become more insecure with unscheduled power flows and higher losses. In this context to overcome the technical difficulty related to power system security, a new concept has been introduced to power system operation and control called Flexible Alternative Current Transmission System (FACTS). The main objective of the different FACTS technology is to bring a system under flexible control and to transmit power as ordered by the control centre. In other term, this new technology allows to increase the power system security at severe loading conditions and critical situations (Contingency). This thesis gives an insight on the application of hybrid parallel global optimization methods based: Genetic Algorithm, Particle Swarm Optimization,and Fuzzy logic, to enhance the optimal power flow solution with consideration of multi type FACTS Controllers.This thesis will be especially useful to graduate students, academic researchers, and engineers specialized in power system operation and control.
Includes bibliographical references.
Keywords: Electric power systems